GŁÓWNE NURTY IDEOLOGICZNO-METODOLOGICZNE W ŚRODOWISKU WARSZAWSKICH PRAWNIKÓW PRZED WYBUCHEM POWSTANIA LISTOPADOWEGO - Pomianowski, Piotr (Zeszyty Prawnicze, 2016)
THE MAIN IDEOLOGICAL AND METHODOLOGICAL STREAMS AMONG WARSAW JURISTS IN 1820S Summary The text concerns the main streams in legal thought in Warsaw in Times of constitutional Kingdom of Poland (Congress Poland: 1815-1830). It is based especially on articles published in Themis Polska which was issued between 1828 and 1830 in Warsaw by young and well-educated lawyers. In Polish legal thought of those times none of philosophical schools had dominant position. However four most important streams may be indicated. The first was a school of natural law, similar to the first understanding of this notion in Enlightenment. Representatives of this stream believed in existence of natural rules of law, which are universal and should be used in any time and in any part of the world. They claimed that statutory law should be only a declaration of natural law. The second direction was école de l’exégèse. Followers of this view gave first position to statutory law. They treated jurisprudence only as a method of interpretation of statutes. Third was historical school. Its adherents treated law like a product of the history of the particular nation and claimed that it is impossible to create universal and rational law. The last of important streams was represented by critics of historical school. They were the followers of Hegel and believed that law, likewise each other social phenomenon, is a product of rational and indispensable historical process. The analysis presented in the text shows that polish legal thought in 1820s was a reflection of ideas originated from the West Europe. The environment of Warsaw jurists in those times was diverse in opinions concerning the nature of law with no one dominant school.